2006
DOI: 10.4103/0970-4388.27893
|View full text |Cite
|
Sign up to set email alerts
|

The effect of tongue appliance on the nasomaxillary complex in growing cleft lip and palate patients

Abstract: Midfacial deficiency is a common feature of cleft lip and palate patients due to scar tissue of the lip and palate closure procedure. The aim of this study was to evaluate the effectiveness of the physiological force of the tongue to move the maxilla in forward position. This research has been done experimentally by, before and after treatment following up in private practice. Ten patients (6 female, 4 male) with complete bilateral cleft lip and palate were selected. All of them had Cl III malocclusion with ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…Maxillary deficiency may be a reflection of the underlying skeletal abnormality for which growth modification and redirection may be indicated with a protraction headgear. Treatment approach to improve the midface deficiency was achieved by using the face mask [2,27], tongue appliance [6], tongue plate [27], protraction head gear [3,28], suborbital protraction appliances [4], ankylosed teeth [29], endosseous implants [30], and surgically assisted orthopedic protraction and distraction osteogenesis [8]. Jamilian et al [6] evaluated the effectiveness of tongue appliance on deficient maxilla in growing cleft lip and palate patients.…”
Section: During Mixed Dentitionmentioning
confidence: 99%
See 3 more Smart Citations
“…Maxillary deficiency may be a reflection of the underlying skeletal abnormality for which growth modification and redirection may be indicated with a protraction headgear. Treatment approach to improve the midface deficiency was achieved by using the face mask [2,27], tongue appliance [6], tongue plate [27], protraction head gear [3,28], suborbital protraction appliances [4], ankylosed teeth [29], endosseous implants [30], and surgically assisted orthopedic protraction and distraction osteogenesis [8]. Jamilian et al [6] evaluated the effectiveness of tongue appliance on deficient maxilla in growing cleft lip and palate patients.…”
Section: During Mixed Dentitionmentioning
confidence: 99%
“…The more posterior the crib, the greater pressure will be. Jamilian et al [6] reported that the anterior part of maxillary plane moved superiorly (anteinclination) and posterior part of it relocated inferiorly. In other words, the maxillary posterior segment is extruded slightly and that is why the lower jaw rotated in a clockwise direction.…”
Section: During Mixed Dentitionmentioning
confidence: 99%
See 2 more Smart Citations
“…Numerous appliance designs such as endosseous implants [1], ankylozed teeth [2], surgically assisted orthopedic protraction [3], distraction osteogenesis [4,5], Hybrid Hyrax appliance [6], reverse chin cup [7,8], face mask [9], tongue appliance [10][11][12], and tongue plate [13] have been used for treatment of skeletal Cl III malocclusions. Forward displacement of the maxilla, labial tipping of the maxillary incisors, counter clockwise rotation of the palatal plane, inhibition of anterior mandibular growth, increase of face height, clockwise rotation of the mandible and lingual tipping of the lower incisors have all been shown to take place [14][15][16].…”
Section: Introductionmentioning
confidence: 99%